2017
DOI: 10.1186/s40510-017-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertical skeletal changes after extraction and non-extraction treatment in matched class I patients identified by a discriminant analysis: cephalometric appraisal and Procrustes superimposition

Abstract: BackgroundIn the long-lasting debate of extraction versus non-extraction treatment, the impact of extractions on the skeletal vertical dimension remains rather unclear. The aim of this retrospective research study was to obtain a bias-free sample of morphologically similar borderline patients treated with or without extraction of the four first premolars and to retrospectively evaluate the vertical changes that occurred.MethodsA borderline sample of 83 patients, 41 treated with four first premolar extractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…Both groups showed a predominant hyperdivergent growth pattern. These findings were expected considering that previous studies have indicated four first premolar extraction in patients with hyperdivergent pattern [48][49][50] . The control of the vertical dimension was thought to occur by a counterclockwise rotation of the mandible through the forward movement of posterior teeth.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Both groups showed a predominant hyperdivergent growth pattern. These findings were expected considering that previous studies have indicated four first premolar extraction in patients with hyperdivergent pattern [48][49][50] . The control of the vertical dimension was thought to occur by a counterclockwise rotation of the mandible through the forward movement of posterior teeth.…”
Section: Discussionsupporting
confidence: 79%
“…Hyperdivergent patients are usually treated with extractions, due to the better vertical control by a counterclockwise rotation of the mandible through the forward movement of posterior teeth . Despite the absence of significant vertical changes reported between extraction and nonextraction treatments, greater vertical development is expected with nonextraction approaches BEIT et al, 2017). Vertical component analysis showed a significantly increased LAFH for group 2, which is in accordance with other studies that indicated extractions in patients with increased LAFH BEIT et al, 2017).…”
Section: Acknowledgmentsupporting
confidence: 88%
See 3 more Smart Citations